Some characterizations of small projective modules - Hà, Nguyễn Thị Thu (Hue University Journal of Science: Natural Science, 2020)
The aim of this paper is to introduce a generalization of projective modules, that is small projective modules. We give some new results on this kind of module and obtain some characterizations of some related rings. Then, we show the relationship between small projective modules and automorphism-coinvariant modules. The results in the article was introduced in [1]. Here, we add examples and clearly demonstrate the prove of some unproven results in the above article.